Tensions Between the Factual and Fictional Discourses in Colonial Narratives: Masking Strategies in Naufragios 1542 by Alvar Nunez Cabeza de Vaca and Infortunios de Alonso Ramirez 1690 by Carlos Siguenza y Gongora - Hachim-Lara, L; Hurtado-Ruiz, P (UNIV PITTSBURGH, UNIV LIBRARY SYSTEM, 2018)
This paper is based on the assumption that narratives are ongoing experiences, actions and processes that take place during the Colonial period. On these grounds, two narrative texts from the beginnings of the colonial formation period will be discussed. Narratives during this period when a vernacular, creole consciousness was being shaped are coherent with the narrations found in travel journals, relaciones and chronicles. A synthesis of factual and fictional discourses arises in these texts that represent not only the identity transformations of the Indian Spanish individual but also the emerging local, creole subjectivity that defines the new culture and its relations with indigenous world. We suggest a first stage in this cultural synthesis that includes two texts that have not been addressed literary and historiographic studies: Naufragios [1542] by Alvar Nunez Cabeza de Vaca and Infortunios de Alonso Ramirez [1690] by Carlos de Siguenza. These two founding narratives used a factual discourse that masked the fictional strategies that were later included in the textual practices that characterize the literatures of the Americas.